An Interdisciplinary Human-Environmental Examination of Effects Consistent with the Anthropocene in the Lower Illinois River Valley. Issue 3 (2nd September 2017) - Colaninno, Carol E.; Chick, John H.; Martin, Terrance J.; Painter, Autumn M.; Brown, Kelly B.; Dopson, Curtis T.; Enzerink, Ariana O.; Goesmann, Stephanie R.; Higgins, Tom; Knutzen, Nigel Q.; Laute, Erin N.; Long, Paula M.; et al.
ABSTRACT: Using archaeological and ecological data of animal communities, and fish communities in particular, we test for evidence consistent with the Anthropocene in the lower Illinois River valley across millennia. Environmental impacts by preindustrialized peoples may be minor compared to current alterations; however, this hypothesis is untested and should be assessed. Using the relative abundance of fish taxa, we tested for differences among archaeological and modern time periods, taking advantage of published zooarchaeological data sets and newly analyzed data. Collections from all archaeological time periods differed significantly from modern collections, but the relative abundance of fishes did not differ significantly among archaeological time periods. Sociopolitical context, material culture, plant-based subsistence patterns, and the use of animal classes shifted temporally, but these differences did not extend to the relative abundance of fish families. Our results suggest that dominating human influences on fish communities did not occur prior to the Late Woodland period in the lower Illinois River.